Assessing the Social Impact of Microfinance in Kaski District, Nepal: Mediating Role of Financial Literacy - Bhandari, Bishnu Prasad; Acharya, Tara Nath (Prithvi Journal of Research and Innovation, 2025)
This study examines the mediating role of financial literacy between access to microfinance and its social outcomes, particularly focused on education, healthcare awareness, and social capital formation. This study was conducted in the Annapurna rural municipality and Pokhara Metropolitan City of Kaski district among 165 microfinance beneficiaries. Quantitative data were collected through a structured questionnaire on 5-point Likert scale from the selected respondents. Descriptive, explanatory and cross sectional research design was employed. also analyze the direct effect and indirect effect of a with financial literacy as a mediating variable. Cross-sectional survey was conducted among 165 microfinance beneficiaries in Kaski District. Study results show that access to microfinance directly impacts social capital formation but has no direct effect on education and healthcare awareness. Financial literacy partially mediates the relationship between access to microfinance and social outcomes. Findings conclude that integrating financial literacy into microfinance services is essential to achieve social goal of microfinance.